Three-dimensional structure of Megabalanus rosa cement protein 20 revealed by multi-dimensional NMR and molecular dynamics simulations - Mohanram, Harini (2021)
Barnacles employ a protein-based cement to firmly attach to immersed substrates. The cement proteins (CPs) have previously been identified and sequenced. However, the molecular mechanisms of adhesion are not well understood, in particular, because the three-dimensional molecular structure of CPs remained unknown to date. Here, we conducted multi-dimensional nuclear magnetic resonance (NMR) studies and molecular dynamics (MD) simulations of recombinant Megabalanus rosa Cement Protein 20 (rMrCP20). Our NMR results show that rMrCP20 contains three main folded domain regions intervened by two dynamic loops, resulting in multiple protein conformations that exist in equilibrium. We found that 12 out of 32 Cys in the sequence engage in disulfide bonds that stabilize the β-sheet domains owing to their placement at the extremities of β-strands. Another feature unveiled by NMR is the location of basic residues in turn regions that are exposed to the solvent, playing an important role for intermolecular contact with negatively charged surfaces. MD simulations highlight a highly stable and conserved β-motif (β7-β8), which may function as nuclei for amyloid-like nanofibrils previously observed in the cured adhesive cement. To the best of our knowledge, this is the first report describing the tertiary structure of an extracellular biological adhesive protein at the molecular level. This article is part of the theme issue 'Transdisciplinary approaches to the study of adhesion and adhesives in biological systems'.